Evaluating the Role of Individualized Homoeopathic Treatment in the Management of Haemorrhoids: A Case Study - Dr. Samir Gupta; Dr. Kirtida Desai; Dr. Krishna Raj; Dr. Poorav Desai; Dr. Mayank Yadav (The Bioscan, 2025)
Piles, medically known as haemorrhoids, are among the most common anorectal conditions, affecting a large proportion of the population worldwide. Although not generally life-threatening, they often present with bleeding, pain, itching, and discomfort that can significantly impair day-to-day functioning and quality of life. Conventional options such as lifestyle modifications, topical preparations, or surgical procedures are available, yet many patients prefer less invasive, holistic approaches. Homoeopathy, with its individualized system of prescribing, has shown potential benefits, especially when combined with dietary regulation and supportive measures. This case report describes the management of a patient with haemorrhoids treated with the homoeopathic remedy Nux vomica. Prescription was based on a thorough case analysis, taking into account both physical complaints and general health. Alongside dietary guidance and auxiliary advice, the individualized medicine led to a notable reduction in bleeding, pain, and discomfort. Symptomatic improvement was observed within a short span of treatment, and no side effects were reported. The findings from this case highlight the scope of individualized homoeopathic treatment in haemorrhoids. When integrated with simple lifestyle measures, it may provide safe and effective relief while supporting long-term well-being. Further clinical studies could strengthen evidence for its broader application. KEYWORDS: Haemorrhoids, Homoeopathy, Nux Vomica, Proctological symptom score (PSS Score)